On the fluctuating wall-shear stress in zero pressure-gradient turbulent boundary layer flows - Orlu, Ramis; Schlatter, Philipp (Physics of Fluids, 2011)
Recent direct numerical simulation (DNS) results relating to the behavior of the fluctuating wall-shear stress τ+,w,rms in turbulent boundary layer flows are discussed. This new compilation is motivated by a recent article [Wu and Moin, "Transitional and turbulent boundary layer with heat transfer," Phys. Fluids 22, 085105 (2010)], which indicates a need for clarification of the value of τ+,w,rms It is, however, shown here, based on other recent DNS data, that most results, both in boundary layer and channel geometry, yield τ+,w,rms ν0.4 plus a small increase with Reynolds number coming from the growing influence of the outer spectral peak. The observed discrepancy in experimental data is mainly attributed to spatial resolution effects, as originally described by Alfredsson et al. ["The fluctuating wall-shear stress and the velocity field in the viscous sublayer," Phys. Fluids 31, 1026 (1988)]. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21